Teacher attrition in a northern Ontario remote First Nation: a narrative re-storying - Burleigh, Dawn (University of Regina, 2016)
Open access article. Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Unported License (cc BY-NC-ND 3.0) applies Increasing teacher retention in First Nations communities has been identified in the literature as requiring attention. When attrition rates are high and teacher efficacy, quality of student experience, and overall academic achievement is compromised, efforts to mobilize plans for stability are needed. Through a narrative re-storying approach this paper unpacks the challenges and opportunities related to teacher attrition in one remote First Nation community in Northern Ontario. Although teacher attrition is inevitable, it is necessary to re-envision attrition factors as a plan for retention. Community integrated induction and mentorship programming, and continuous and multi-year contracts are two possible approaches to boost retention. Teacher education is also explored as a long-term approach to address teacher attrition from a system perspective. In all approaches, collaborative effort, engagement, and funding are needed from the federal government, local education authorities, and faculties of education to increase teacher retention in remote First Nation communities. Yes